Climate change and perspectives for Peru of the Paris Agreement - Ruiz Muller, Manuel (2017)
Regardless of the difficult scenario facing the Paris Agreement with the recent withdrawal of the US, Peru will continue to comply with its international obligations and consolidating its national policies and frameworks related to climate change. Although Peru entered the international negotiation process late – basically from COP 20 onwards- it has had a decisive participation and influence in its outcome, the Paris Accord. Pero has for over a decade, been developing a robust internal architecture of norms and institutions, to launch the country towards a greener economy. With the difficulties that this means for a developing country like Peru, the future leads inevitably to the search of clean and environmentally friendly and sustainable economies.